Local Wisdom in Traditional Malay Games as a Media for Cultural Preservation and Instilling Character Values of Nationalism in Children - Dewi Kesuma Nasution; Tengku Winona Emelia; Sri Listiana Izar (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This research uses ethnographic qualitative research. The purpose of this study is to examine the form and meaning of local wisdom contained in traditional Malay games in terms of ecolinguistics and preservation strategies that can be done. The data is in the form of descriptions of body movements in the steps of the game and snippets of song lyrics that show the values of local wisdom. Sources of data were children who played traditional Malay games, actors of Malay tradition, and traditional leaders. The data collection method used is the listening and speaking method with note-taking techniques through observation and interviews. The data analysis technique used is data reduction, data presentation, and drawing conclusions. The results showed that the game of injit injit semut, lu lu cina buta, tam tam buku, and wak wak udin has a form of local wisdom in the form of words, namely, poetry that is sung when playing and actions in the form of body movements that are reflected in the steps of the game. The meaning contained in the forms of local wisdom is described in four values, namely 1) the value of togetherness, 2) the value of education, 3) the value of sharing, and 4) the religious value. The game can be preserved by making game applications that can be downloaded on mobile phones with the same original game, and it can be introduced again in educational institutions, so that there will be more research on local wisdom on traditional games.